Dielectric barrier discharge plasma catalysis for CO2 conversion: Recent progress and perspectives - Longmei Li; Xiaohua Chen; Bella; Feiyang Hu; Xiaohua Zhang; Runping Ye; Lei Gong; Rongbin Zhang; Gang Feng; Sibudjing Kawi (Carbon Capture Science & Technology)
In recent years, dielectric barrier discharge (DBD) plasma-catalytic technology has emerged as a promising approach for CO2 conversion due to its unique ability to activate inert molecules under mild conditions. This review systematically summarizes recent advances in DBD plasma-assisted catalytic processes for CO2 utilization, focusing on four major technologies: CO2 methanation, dry reforming of methane (DRM), CO2 hydrogenation to methanol, and the reverse water-gas shift (RWGS) reaction. This review provides a comprehensive examination of DBD plasma-catalytic CO2 conversion, with particular focus on process parameters, reaction mechanisms, and catalyst design strategies. The analysis highlights the crucial plasma-catalyst synergy, where non-equilibrium electron excitation from DBD plasma facilitates CO2 dissociation while precisely engineered catalyst properties, including oxygen vacancies, tailor metal-support interactions, and direct the subsequent conversion pathways. These interdependent effects collectively determine their activity, selectivity, and stability. Additional emphasis is placed on plasma-assisted catalyst synthesis techniques and innovative approaches to mitigate carbon deposition, offering insights into the development of more efficient and durable catalytic systems for CO2 conversion. This review affirms the technical viability and promising prospects of plasma-catalytic CO2 conversion while acknowledging critical challenges in energy efficiency and product selectivity. To accelerate industrial translation, future research should focus on unraveling plasma-catalyst interactions through coupled in situ characterization and computational modeling, establishing fundamental structure-performance relationships under dynamic reaction conditions, and engineering scalable reactor systems that maintain catalytic integrity during continuous operation.